2020
DOI: 10.1029/2020gl088242
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Between Tornadic and Nontornadic Supercells Using Polarimetric Radar Signatures of Hydrometeor Size Sorting

Abstract: Supercell storms are the most prolific producers of violent tornadoes, though only a fraction of supercells produce tornadoes. Past research into the differences between tornadic and nontornadic supercells have provided some insights but are of little utility to a real-time warning decision process. Operational weather radars provide consistent observations in real time, but conventional radar techniques have not been able to effectively distinguish between tornadic and nontornadic supercells. After the nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Recent research has indicated some promising results linking a large Z DR -K DP separation angle to tornadic potential in supercell storms, e.g., [26,37]. In this study, the separation angle is nearly identical between pre-tornadic and pre-TGF storms (Table 4).…”
Section: Comparisons Between Radar Metric Distributionssupporting
confidence: 53%
“…Recent research has indicated some promising results linking a large Z DR -K DP separation angle to tornadic potential in supercell storms, e.g., [26,37]. In this study, the separation angle is nearly identical between pre-tornadic and pre-TGF storms (Table 4).…”
Section: Comparisons Between Radar Metric Distributionssupporting
confidence: 53%
“…Further, regions of enhanced K DP can be censored out if they have reduced values of co‐polar correlation coefficient. As such, we have advocated for using an area‐based approach for identifying low‐level Z DR and K DP enhancement regions in observations (Loeffler & Kumjian, 2018; Loeffler et al., 2020). Loeffler and Kumjian (2018) identified two components of this Z DR − K DP separation which comprised their “separation vector": the distance and orientation of separation.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Loeffler et al. (2020) showed that tornadic supercells tended to have separation orientations closer to perpendicular to storm motion, while nontornadic supercells tended to have orientations closer to parallel to storm motion.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The second uncertainty is the role of updrafts. While both updrafts and storm‐relative winds can lead to sustained size sorting (Kumjian & Ryzhkov, 2012), previous studies (e.g., DMR15; LDL20; Loeffler et al., 2020) mostly focused on storm‐relative winds. These studies implicitly assumed that the effect of storm‐relative winds overwhelmed that of the updrafts.…”
Section: Introductionmentioning
confidence: 99%